2016
DOI: 10.1177/0162643416681161
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships Enhancing Practice

Abstract: In higher education, current teaching evaluation models typically involve senior faculty evaluating junior faculty. However, there is evidence that peer-to-peer junior faculty observations and feedback may be just as effective. This descriptive case study utilized an inductive analysis to examine experiences of six special education early career faculty, from different institutions, using the partnerships that enhance practice (PEP) model for technology-based observations of teaching in higher education. PEP p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In line with the framework synthesis method, we refined the initial categories to include several themes and topics that appeared during the analysis. The results of the empirical review served to address the research questions of how collegial approaches to faculty development were described in the research literature and what factors shaped those Bulman et al, 2016;Byrne et al, 2010;Carroll & O'Loughlin, 2014;Chamberlain et al, 2011;Costello et al, 2001;Davis, 2011;de Lange & Wittek, 2018;Georgiou et al, 2018;Hammersley-Fletcher & Orsmond, 2004, 2005Hatzipanagos & Lygo-Baker, 2006;Hendry et al, 2014;Hubball & Clarke, 2011;Kell & Annetts, 2009;Kenny et al, 2014;Mager et al, 2014;O'Keefe et al, 2009;Pattison et al, 2012;Servilio et al, 2017;Shortland, 2004Shortland, , 2010Shousha, 2015;Sti...…”
Section: Factors That Shape Collegial Faculty Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the framework synthesis method, we refined the initial categories to include several themes and topics that appeared during the analysis. The results of the empirical review served to address the research questions of how collegial approaches to faculty development were described in the research literature and what factors shaped those Bulman et al, 2016;Byrne et al, 2010;Carroll & O'Loughlin, 2014;Chamberlain et al, 2011;Costello et al, 2001;Davis, 2011;de Lange & Wittek, 2018;Georgiou et al, 2018;Hammersley-Fletcher & Orsmond, 2004, 2005Hatzipanagos & Lygo-Baker, 2006;Hendry et al, 2014;Hubball & Clarke, 2011;Kell & Annetts, 2009;Kenny et al, 2014;Mager et al, 2014;O'Keefe et al, 2009;Pattison et al, 2012;Servilio et al, 2017;Shortland, 2004Shortland, , 2010Shousha, 2015;Sti...…”
Section: Factors That Shape Collegial Faculty Developmentmentioning
confidence: 99%
“…Bell & Mladenovic, 2008;M. Bell & Cooper, 2013;Buchanan & Parry, 2019;Bulman et al, 2016;Byrne et al, 2010;Carroll & O'Loughlin, 2014;Davis, 2011;de Lange & Lauvås, 2018;Deni & Malakolunthu, 2013;Hammersley-Fletcher & Orsmond, 2004, 2005Kell & Annetts, 2009;O'Keefe et al, 2009;Quinlan & Åkerlind, 2000;Servilio et al, 2017;Shortland, 2010;Shousha, 2015;Thampy et al, 2015;Torres et al, 2017;Wildman et al, 2000;Wingrove et al, 2015;Wingrove et al, 2018;Yiend et al, 2014 Group size Pairs (20) A. Bell & Mladenovic, 2015;…”
Section: Factors That Shape Collegial Faculty Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Over recent decades, peer review of teaching (PRT) has become an important mechanism for improving the quality of teaching in higher education (HE). While there is considerable international research on PRT outcomes (Lomas & Nicholls, 2005;Servilio et al, 2017;Yurtseven & Altun, 2018), these are not widely reported within Australian universities (Burrows et al, 2011;Lomas & Kinchin 2006). Efforts to undertake PRT in the Australian tertiary sector have generally been informal small-scale projects, where results are often not published (Harris et al, 2008).…”
Section: Introductionmentioning
confidence: 99%